White matter hyperintensities in late life depression: a systematic review. - Herrmann, L; Le Masurier, M; Ebmeier, K (2008)
BACKGROUND: White matter hyperintensities in MRI scans are age related but appear to be more prevalent in depressed patients. They may be more pronounced in late onset depression. This finding, if confirmed, would potentially illuminate the heterogeneity of depression in elderly subjects. METHODS: We conducted a systematic literature search of studies investigating white matter changes in late life depression, identifying 98 studies. The 30 remaining eligible studies were scrutinised for the presence and severity measures of periventricular and deep white matter changes in late life, late onset and, if available, early onset depression as well as in controls. Comparisons between groups were entered into random effects meta-analyses using odds ratios and Cohen's d, as appropriate. Correlations with potential confounders, such as age difference between groups, were explored. RESULTS: Late life depression and, to a greater extent, late onset depression in late life were characterised by more frequent and intense white matter abnormalities. In particular, the odds of having white matter changes were over 4 for late compared with early onset depression. Similarly, on severity scales, late onset depression had scores of 0.7-0.8 standard deviations above early onset patients. CONCLUSIONS: Significant differences between early and late onset depression suggest different aetiological mechanisms, in accordance with a theory of "cerebrovascular" depression of late onset. Greater duration of depressive symptoms, signs and treatment does not appear to have a measurable impact on white matter signal in MRI scans.